From the Isles of the Blessed to Taprobane - Székely, Melinda (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
By analysing Pliny’s Naturalis Historia and placing it in the broader context of ancient knowledge, I describe the knowledge and myths about the islands of the western and eastern edges of the known world in antiquity, with particular reference to Pliny’s subjective ideas.